A Global System for Mobile Communications (GSM) Module is Using in Smart Home Security Systems (International Journal of Food and Nutritional Sciences, 2022)
Security is a growing concern for everyone. Home security is becoming more and more important in today's world as the risk of infiltration rises daily. Home security systems were created to protect homes from intruders and are necessary for convenience and safety. The problem arises in traditional system such as lack of monitoring of gas leakage, and accidents due to fire in their house. Hence author focusses on the GSM is using in smart home security system which provides using GSM technology, the owner of the house or business receives remote notification through SMS. It concluded that the mobile network has been used in the design and testing of the GSM-based home security system. Through use of GSM technology, the users may get notifications from anywhere, making the system position independent. In future them, they may use a GPRS modem in addition to a GSM modem to connect to the internet and improve our project's IOT potential. The sensor may be linked to an IOT cloud server, as well as the video that is collected may also be transmitted through an internet protocol towards the cloud server.